Household-Scale Biodigester Application: Transforming Livestock Waste into a New Source of Income in Kasembon Subdistrict - Kilawati, Yuni; Amrillah, Attabik Mukhammad; Maimunah, Yunita; Kartikasari, Dany Primanita; Muttaqin, Adharul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2026)
Livestock farmers in Kasembon Subdistrict face dual challenges: severe environmental pollution from dumping manure directly into rivers, and economic strain due to high dependence on costly LPG and synthetic fertilizers. This community service program introduces household-scale biodigesters to solve both environmental and economic issues simultaneously. Involving 20 local participants through the Participatory Rural Appraisal (PRA) method, capacity building, and technical assistance, the intervention yielded highly significant outcomes. LPG consumption plummeted from 3.8 to 0.4 cylinders monthly. Behavior completely transformed: previously, 80% of farmers polluted water bodies, whereas today 100% utilize their waste as biodigester feedstock, effectively halting river pollution. Economically, this circular system generates average monthly savings of Rp 206,000 per household by substituting LPG and chemical fertilizers. Participants' technical skills also surged from 1.95 to 4.61. Ultimately, biodigester technology successfully mitigates environmental damage while empowering rural communities toward sustainable energy independence and food security